Social responsibility policy implementation on upstream oil and gas industry (Study on Saka Indonesia Pangkah Limited in Gresik Regency East Java). - Crenantoro, Endro Probo (JPAS (Journal of Public Administration Studies), 2017)
Abstract. This study aims to describe the policy implementation of CSR program based on corporate vision and mandate of Oil and Natural Gas Law No. 22 of 2001. It also shows the community acceptance to the CSR programs that have been done. This study used qualitative method with descriptive research type. The unit of analysis taken is the corporate social responsibility program implemented by Saka Indonesia Pangkah Limited (SIPL) on the seven villages in Ujungpangkah and Manyar District, Gresik Regency. The result showed that the policy implementation of CSR through community development program in upstream oil and gas industry did not have standard operating procedure (SOP) yet that can be used as guidance by Production Sharing Contract (PSC) in carrying out social responsibility program in their operational area, even though it has strong legal basis in the form of Oil and Gas Law no. 22 of 2001. SIPL has implemented corporate social responsibility program based on Oil and Gas Law no. 22 of 2001 through various model approaches based on community need assessment referring on the concept of triple bottom line around the operation area. Thus, local community acceptance of the program is relatively acceptable. Finally, the main strategy of the CSR program run by SIPL aims to secure the company's operations.Â Keywords: Policy Implementation, Corporate Social Responsibility, Community Development.